Mr. A Study on Marketing Strategy of Nestle in Asia - editor aibpm; Xuan Choo Tze; Xin Chong Zhe; Chian Chong Sin; Hern Chu Shieh (Advances in Global Economics and Business Journal, 2022)
Nestle is the world's leading health, nutrition, and wellness firm, headquartered in Switzerland. It is the largest food and beverage company globally with a revenue of US$89.772 billion in 2015. Nestle employs nearly 339,000 employees and has 447 factories in 180 nations. Nestle is also the most successful leading producer of high-quality, nutrient-dense food and beverages for Asian consumers. It sells about 2000 various brands across seven main food and beverage categories. Nestle places a premium on quality and safety for its customers. Nestle has developed useful marketing strategies to motivate consumers to buy their products. This study aims to determine Nestle's most effective marketing strategies in Asia. The findings underlined that Nestle’s marketing strategy includes market segmentation, targeting, differentiation, and positioning.